ADVANCING THE STATE OF THE ART IN L2 SPEECH PERCEPTION-PRODUCTION RESEARCH: REVISITING THEORETICAL ASSUMPTIONS AND METHODOLOGICAL PRACTICES - Nagle, Charles L.; Baese-Berk, Melissa M. (Studies in second language acquisition, 2022)
One of the basic goals of second language (L2) speech research is to understand the perception-production link, or the relationship between L2 speech perception and L2 speech production. Although many studies have examined the link, they have done so with strikingly different conceptual foci and methods. Even studies that appear to use similar perception and production tasks often present nontrivial differences in task characteristics and implementation. This conceptual and methodological variation makes meaningful synthesis of perception-production findings difficult, and it also complicates the process of developing new perception-production models that specifically address how the link changes throughout L2 learning. In this study, we scrutinize theoretical and methodological issues in perception-production research and offer recommendations for advancing theory and practice in this domain. We focus on L2 sound learning because most work in the area has focused on segmental contrasts.